Paul and first-century letter writing : secretaries, composition and collection - Richards, E. Randolph (Ernest Randolph) (Downers Grove, Ill. : InterVarsity Press, 2004)
Publisher's description: Traditional Christian art depicts Paul the letter writer, pensive and pen in hand, attentive to the Spirit. Contemporary students of Paul might imagine him pacing in agitation as he rapidly dictates to a secretary his letter to the Galatians. But in reality neither of these pictures is accurate. Randolph Richards gives us a truly informed look at the letter-writing process in Paul's day and offers a new and intriguing perspective on how this important portion of Christian Scripture came to be.
Introduction -- 1. A modern, Western Paul -- 2. Paul as a first-century letter writer -- 3. The tools of a letter writer -- 4. Secretaries in the first-century world -- 5. Paul's use of a secretary -- 6. Identifying inserted material -- 7. Weaving together a letter -- 8. Classifying Paul's letters -- 9. Analyzing Paul's writing style -- 10. Preparing a letter for dispatch -- 11. Dispatching the letter -- 12. Paul's letter carriers -- 13. Paul's use of his letter carriers -- 14. Collecting Paul's letters -- 15. Inspiration and first-century letter writing -- Conclusion.
Includes bibliographical references (p. 233-244) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Classical letters -- History and criticism; Letter writing, Classical